Membangun Kesadaran Lingkungan, Pendidikan dan Literasi Digital di Desa Belawang Kabupaten Barito Kuala - Faridah Humairo; Khairussalam; Maya Isti; Dina Amalina; Patrisius Ronald Dalanggali; Dine Bunata; Muhammad Dwi Handoko (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2023)
Belawang Village, situated on the banks of the Barito River in the Belawang District, faces significant challenges related to environmental awareness and information access. The primary issues plaguing the village involve widespread littering of trash throughout the area and the absence of a village website. In tackling these issues, the dedicated team has focused on two fundamental aspects: environmental education and community-based waste management. Their activities encompass the dissemination and training regarding the importance of waste separation and environmental care, targeting age groups from elementary school children to high school students. Additionally, they have established adequate trash bins to discourage reckless disposal. Through these efforts, the community-based waste management program has successfully transformed the mindset of the younger generation, enhanced their understanding of waste separation's significance, and substantially reduced litter. The collaboration with local village authorities and the youth has been a key factor contributing to the program's success. The outcomes include heightened environmental consciousness among the community, a noticeable reduction in litter, and improved information access via the village website. Furthermore, the program has provided a deeper understanding of the importance of higher education to the younger generation, opening doors to better career opportunities and empowering them to pursue their aspirations. This service program exemplifies genuine efforts to create a cleaner, healthier, and sustainable environment in Belawang Village while delivering long-term benefits in education and information access for the entire community.